P11.14.A Systematic review of phase III trials in newly diagnosed glioblastoma 2005-2021. (5th September 2022) - Oster, C; Lazaridis, L; Feldheim, J; Schmidt, T; Kleinschnitz, C; Kebir, S; Glas, M
Abstract: Background: Despite a plethora of studies since the EORTC/NCIC trial in 2005, glioblastoma (GBM) prognosis remains poor. We here identify and compare glioblastoma phase III trials in terms of efficacy and baseline characteristics in an attempt to summarize the experience of the past 16 years. Methods: A systematic literature search using PubMed and ClinicalTrials.gov was conducted to provide an overview of clinically relevant GBM phase III trials (years 2005-2021) of adult patients younger than 70 years of age. Search results were screened according to predefined inclusion criteria and either excluded or included in further analysis on study design, baseline characteristics, and survival results. Results: Eleven trials from the literature and clinical trial database fulfilled the search criteria. Among these trials, a total of three GBM phase III trials reported overall survival (OS) benefit, including the EORTC/NCIC study (NCT00006353), EF-14 (NCT00916409) and CeTeG/NOA09 (NCT01149109). All three studies demonstrate similar hazard ratios, which translate into risk reduction of about 40%. Furthermore, low toxicity profile and mostly preserved quality of life were attributed to the treatments tested. Looking at the study designs, eight out of eleven trials were open label randomized trials, including all of the positive ones, and only three negative trials employed treatment blinding and a placebo control. Canonical baseline characteristics (extent of resection, age, gender, MGMT promoter methylation status) did not significantly differ between positive and negative trials. IDH mutation status was analyzed in only two trials, each showing a small percentage of IDH-mutant tumors only. Conclusion: This analysis on GBM phase III trials conducted between 2005 and 2021 revealed that the majority of trials did not show a significant improvement in overall survival. CeTeG/NOA-09 and EF-14 are the only two studies with positive overall survival outcome since the EORTC/NCIC trial in 2005.